Penerapan Massage Effleurage terhadap Penurunan Nyeri Akut Punggung Bawah pada Ibu Hamil Trimester III - Eni Folendra Rosa; Wiwice Arianti; M Agung Akbar (NHM PRESS, 2023)
In the process of pregnancy there is a condition experienced by pregnant women in the third trimester, namely back pain. One of the pain management that provides a relaxing effect and reduces pain is Effleurage Massage. This study aims to describe pain management in third trimester pregnant women with acute low back pain. This study used a case study method with a nursing process approach. The main intervention for pain management with Effleurage massage is carried out once a day for 3 consecutive days with a duration of ± 15 minutes. This research was conducted in Tanjung Agung Health Center. The results showed that after three days of the Effleurage massage intervention there was a decrease in the pain scale on Client 1 from pain scale 5 and Client 2 from Pain Scale 6 to a change in the same pain scale, namely scale 1. The researcher concluded that the implementation of pain management nursing, especially effleurage massage, showed the effectiveness of reducing the pain scale for clients at the Tanjung Agung Health Center. Effleurage massage techniques can be given to third trimester pregnant women with back pain problems to reduce pain intensity and increase the comfort of pregnant women.